Undrained behavior of sand under cyclic paths that match storm-wave loading conditions. Issue 1 (2nd January 2018) - Pan, Kun; Yang, Zhongxuan
ABSTRACT: In ocean engineering, storm-wave loading imposes irregular cycles in the magnitudes acting on the coastal or seabed cohesionless soils, giving rise to more complex consequences on the their liquefaction susceptibility, compared with those under uniform cyclic loadings that were considered in most routine engineering designs. This paper presents a systematic experimental investigation into the undrained behavior of saturated loose sand subjected to irregular cyclic triaxial paths that match the storm-wave loading conditions, with the presence of static shear stress that mimics the initial condition of sand deposits in the field, along with the conventional uniform cyclic triaxial tests for comparison. The results indicate that both the initial static stress and the cyclic irregularity influence the pore pressure development and cyclic resistance of sand. When the static shear stress presents, the sand samples under storm-wave loading show a monotonic increase in cyclic resistances to liquefaction. In addition, the concept of strain energy is used to delineate the accumulation of pore pressure during cyclic loading. A unique relationship between the normalized pore pressure and the strain energy is observed, irrespective of the static stress level, cyclic stress amplitude, and applied cyclic loading patterns.